(untitled) (Педагогіка вищої та середньої школи, 2008)
In the article is presented the characteristic of strategy and models of the overcoming conduct in the untypical situation of professional activity. Analyzed the influence of its conduct on professional reliability of specialists of sothionomic sphere activity.